Human lagochilascariasis-A rare helminthic disease. - Dulcinea Maria Barbosa Campos; Alverne Passos Barbosa; Jayrson Araújo de Oliveira; Giovana Galvão Tavares; Pedro Vitor Lemos Cravo; Alejandro Luquetti Ostermayer (PLoS Neglected Tropical Diseases)
Lagochilascariasis is a parasitic disease caused by a helminth of the order Ascaroidea, genus Lagochilascaris that comprises 6 species, among which only Lagochilascaris minor Leiper, 1909, is implicated in the human form of the disease. It is remarkable that the majority of cases of human lagochilascariasis in the Americas have been reported in Brazil. The natural definitive hosts of this parasite seem to be wild felines and canines. Lagochilascariasis is mostly a chronic human disease that can persist for several years, in which the parasite burrows into the subcutaneous tissues of the neck, paranasal sinuses, and mastoid. L. minor exhibits remarkable ability to migrate through the tissues of its hosts, destroying even bone tissue. Fatal cases have been described in which the parasite was found in the lungs or central nervous system. Treatment is often palliative, with recurrence of lesions. This paper summarizes the main features of the disease and its etiologic agent, including prevalence, life cycle, clinical course, and treatment.